Understanding the mechanism of DNA threshold elongation: Свойства нелинейных биофизических систем со сложной внутренней структурой - Volkov, Sergey N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
The mechanism of threshold elongation of DNA macromolecule (overstretching) is studied within the frame-work of phenomenological approach, accounting both external (stretching) and internal (conformational) dis-placement components. As shown, the overstretching of DNA under the action of an external force can occur in two stages. Firstly, due to the coupling between the components, at a some critical value of external force a conformational bistability is formed in the macromolecule structure. In turn, the appearance of bistability stimulates the formation of domains in the DNA chain with two different conformations (B and S). Secondly, under favorable boundary conditions, the conformationally induced deformation acquires the possibility to propagate along the macromolecule as domain walls. In this way the bistability occurrence in the macromolecule conformation provides a threshold effect of elongation. The calculated contributions in DNA overstretching show agreement with the observed data, and allow to explain the dependence of macromolecule threshold elongation on nucleotide content.